G protein‐coupled estrogen receptor is involved in modulating colonic motor function via nitric oxide release in C57BL/6 female mice. Issue 3 (12th December 2015) - Li, Y.; Xu, J.; Jiang, F.; Jiang, Z.; Liu, C.; Li, L.; Luo, Y.; Lu, R.; Mu, Y.; Liu, Y.; Xue, B.
Abstract: Background: Estrogen may regulate gastrointestinal motor functions, but the mechanism(s) is not totally understood. Here, we investigated whether G protein‐coupled estrogen receptor (GPER/GPR30) was involved in regulating colonic motor functions and explored the underlying physiological mechanisms. Methods: Adult female C57BL/6 mice were used. The expression and localization of GPER were examined by RT‐PCR, western blot, and immuno‐labeling. The role of GPER in modulating colonic motor functions was assessed by the bead propulsion test in vivo and organ bath experiments in vitro . Key Results: GPER was expressed in colonic myenteric neurons. The colonic transit time (CTT) in proestrus and estrus was significantly longer than that in diestrus. In vivo treatment with the selective GPER blocker G15 significantly shortened CTT in proestrus and estrus. In ovariectomized mice, acute estrogen supplementation increased CTT, which could be abolished by G15 co‐administration. The GPER agonist G‐1 caused a concentration‐dependent inhibition of carbachol ‐induced circular muscle strips contraction, which was abolished by tetrodotoxin and the neuronal nitric oxide synthase (nNOS) inhibitor N ‐propyl‐l ‐arginine. G‐1 stimulated NO production in isolated longitudinal muscle myenteric plexus and cultured myenteric neurons, which was dependent on nNOS. Immunofluorescence labeling showed co‐localization of GPER with nNOS in the myenteric plexus. Conclusions & Inferences: We suggest that activation of GPER exerts an inhibitory effect on colonic motility by promoting NO release from myenteric nitrergic nerves. These results raise a possibility that GPER may be involved in mediating the inhibitory effect of estrogen on colonic motor functions, via a non‐genomic, neurogenic mechanism. Abstract : GPER is expressed in colonic myenteric neurons and co‐localized with nNOS, its activation inhibits colonic propulsion in vivo and the contractile response in circular smooth muscle in vitro . The inhibitory effects of GPER may be mediated by promoting NO release from myenteric nitrergic nerves.